IMPROVEMENT OF BUSINESS PROCESS MODELING IN SMALL AND MEDIUM INDUSTRIES (SMIS) TO SUSTAIN IN GLOBAL ECONOMIC COMPETITION - Agung Haryono; Erry Rimawan (Operations Excellence: Journal of Applied Industrial Engineering, 2017)
The objective of this research is to analyze how Business Process Modelling (BPM) can be develop and improve in SMIs. Business Process Modeling have been the one of important strategy adopted by organizations around the world especially in Small and Medium Industries to sustain in global economic competition 2017. Successful implementation of these depends on applicability and business functional process effectiveness. BPM success also depends on organizational Business Process Improvement (BPI). This paper presents a benchmark process of BPM in Small and Medium Industry (SMI) perspectives especially in Steel fabricator SMI. And it creates new BPM in other SMI to become lean business in organizational structural. It includes a review of financial performance in SMI to decrease business process cost and get higher profit, findings of research accomplished via interviews with people in board of director and shareholder.